Distinct Light-Mediated Pathways Regulate the Biosynthesis and Exchange of Isoprenoid Precursors during Arabidopsis Seedling Development - Rodríguez-Concepción, Manuel (American Society of Plant Biologists, 2004)
Plants synthesize an astonishing diversity of isoprenoids, some of which play essential roles in photosynthesis, respiration, and the regulation of growth and development. Two independent pathways for the biosynthesis of isoprenoid precursors coexist within the plant cell: the cytosolic mevalonic acid (MVA) pathway and the plastidial methylerythritol phosphate (MEP) pathway. In at least some plants (including Arabidopsis), common precursors are exchanged between the cytosol and the plastid. However, little is known about the signals that coordinate their biosynthesis and exchange. To identify such signals, we arrested seedling development by specifically blocking the MVA pathway with mevinolin (MEV) or the MEP pathway with fosmidomycin (FSM) and searched for MEV-resistant Arabidopsis mutants that also could survive in the presence of FSM. Here, we show that one such mutant, rim1, is a new phyB allele (phyB-m1). Although the MEV-resistant phenotype of mutant seedlings is caused by the upregulation of MVA synthesis, its resistance to FSM most likely is the result of an enhanced intake of MVA-derived isoprenoid precursors by the plastid. The analysis of other light-hyposensitive mutants showed that distinct light perception and signal transduction pathways regulate these two differential mechanisms for resistance, providing evidence for a coordinated regulation of the activity of the MVA pathway and the crosstalk between cell compartments for isoprenoid biosynthesis during the first stages of seedling development.